The Effect of Service Quality and Product Quality on Indihome Customer Satisfaction in Bandar Lampung City - Ikhbal, Syufalmi; Safira, Yeni; F Sanjaya, Vicky (Terbuka Journal of Economics and Business, 2021)
This study aims to analyze the effect of service quality and product quality on Indihome consumer satisfaction. . The level of customer satisfaction with an item or service will reflect the level of success of the company in marketing its products. So that's why this study was conducted which aims to determine whether the quality of service and product quality affect indihome customer satisfaction in the city of Bandar Lampung. The variables used in this study are service quality, product quality and customer satisfaction. This study uses quantitative methods, with a sample of 30 people. The data was collected using a questionnaire method and hypothesis testing in this study using the SmartPLS 3 program.